Conventional wisdom - Auderset, Alain (Monarch Books, 2006)
Conventional Wisdom throws light on the human condition. In a series of free standing panels, Alain Auderset offers a funny, wacky and creative assessment of the foibles of our species - and the divine response to our blackly fallen state. Alain Auderset is a professional illustrator and cartoonist based in Switzerland, working in French. Subject